Marine Conservation Policies and Tourism Performance in Small Islands: Evidence from Panel Regression in Gili Matra - Riduan Mas'ud; Husni Muhamad Rifqi; Vinson Vano (Advances in Tourism Studies, 2025)
This study examines how marine conservation policy intensity and environmental quality influence tourism performance and island-level income in the Gili Matra Marine Tourism Park, Indonesia. Using a twenty-year fixed effects panel (2005–2024), the analysis evaluates the effects of conservation measures, ecological conditions, regional tourism demand, and accessibility on tourist arrivals and tourism-generated revenue across three small islands. The results show that stronger conservation policies and higher environmental quality significantly increase both arrivals and income, demonstrating that ecological governance functions as an economic asset rather than a constraint. Robustness tests with lagged and interaction models confirm the stability of these relationships and reveal complementarity between policy interventions and environmental improvements. The study contributes to theoretical debates on sustainable island tourism and provides evidence supporting Indonesia’s Blue Economy agenda. Policy recommendations highlight the importance of enforcement, ecological monitoring, transport infrastructure, and resilience planning.